Wordsmith : a guide to college writing - Arlov, Pamela. 4 0 16; 5 (Upper Saddle River, N.J. : Prentice Hall, 2010)
Giving readers the tools and know-how to confidently write an effective essay, this complete, step-by-step guide to the composition and grammar structure of an essay addresses all parts of the classic five-paragraph essay - thesis, introduction, body and conclusion - in separate sections, and includes myriad examples and practice exercises to help hone each element. Direct and conversational, it includes an entire section on grammar, and a selection of twenty readings - complete with reading comprehension questions and writing assignments. Presents the writing steps in the order in which writers use them; i.e., begins with a chapter on prewriting, moves on to individual chapters on the thesis, introduction, supporting paragraphs, and conclusion - then follows through chapters on revising and proofreading. Offers a clear, step-by-step presentation of grammar that is easily referenced. Provides a varied and relatively short selection of readings that can be used for comparison in structure and content. Adds levity and interest to the subject with lighthearted, fun and informative boxes, and motivates users to hone their writing skills with numerous journal, paragraph, and essay writing assignments throughout. For anyone wishing to develop their composition/developmental essay writing skills.
The writing process --;Preparing to write --;Building a framework: thesis and organization --;Introducing the essay --;Developing body paragraphs --;Concluding the essay --;Revising, proofreading, and formatting --;Showing and telling: description, narration, and example --;Limiting and ordering: definition, classification, and process --;Examining logical connections: comparison-contrast, cause-effect, and argument --;Writing a summary --;Writing a research paper --;Verbs and subjects --;Subject-verb agreement --;Coordination and subordination --;Run-on sentences --;Sentence fragments --;Pronoun case --;Pronoun agreement, reference, and point of view --;Misplaced and dangling modifiers --;Parallel structure --;Verb shifts --;Sentences with style --;Commas --;Other punctuation --;Word choice --;Words commonly confused --;Capital letters --;Apostrophes --;Quotation marks, underlining, and italics.
Includes indexes.
Keywords: 2 -- 0; 6; Rhetoric.;Grammar. -- English language;English language;College readers.;Report writing. -- 20; 20; 2